Punching Shear Behavior of Reinforced Concrete Isolated Footings Reinforced with GFRP Rebars - Som, Sothea; Tirapat, Supakorn (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The punching shear strength of isolated footings varies considerably for different codes, partly due to varying amounts of soil reaction considered when calculating the punching shear resistance. The present study aimed to investigate the punching shear behavior of reinforced concrete isolated footings reinforced with GFRP rebars, taking into account soil-structure interaction. Full-scale specimens were divided into two groups based on the type of foundation support and were tested separately. One group was supported on a bed of elastic springs to simulate an elastic foundation based on Winkler-type soil reactions, while the other was supported on a rigid support to examine the effect of soil-structure interaction on the punching shear behavior. The specimens were tested to investigate the load-carrying capacity, failure mode, subgrade reaction, crack development, footing slab deflection, and rebar strain distribution. Results from the tests showed that the elastic spring system maintained a constant k value despite the vertical settlement. Both tested specimens failed in punching shear failure mode, and the specimen supported by the elastic spring system had a little higher punching shear resistance than the one supported on a rigid support. Additionally, the resistance of the specimens exceeded the calculated value according to the ACI code, suggests that the code is reliable and perhaps more conservative.